Global Social Tolerance Index and multi-method country rankings sensitivity - Zanakis, Stelios H; Newburry, William; Taras, Vasyl (Journal of International Business Studies, 2016)
Social tolerance refers to the extent of recognition and acceptance of differences, willingness to grant equal rights, and refraining from openly intolerant attitudes. Utilizing World Value Survey (WVS) data (56 countries, 83,000 usable respondents), we develop a Global Social Tolerance Index (GSTI) that incorporates gender, minority, immigrant, and religion tolerance dimensions. We develop this index using a multi-step data-driven procedure involving five data standardizations, seven weighting approaches, and five aggregation methods. They generate 124 replications for each country’s index and rank, yielding a median overall position and several measures of rank sensitivity/robustness to different weighting, standardization, and aggregation approaches. It builds on prior social tolerance indexes in terms of scope and dimensionality, and avoids problems associated with equal or subjective weighting. The GSTI index/rankings provide a tool for IB scholars to examine nations’ overall tolerance or tolerance regarding each dimension relative to other external criteria. Our procedure can be used to develop other indexes and rankings of nations or organizations within a country or region. In practice, any such non-participatory method should always serve as a starting point to facilitate deliberations of experts and/or decision-makers for policy recommendations.